Effects of Dietary Oleacein Treatment on Endothelial Dysfunction and Lupus Nephritis in Balb/C Pristane-Induced Mice - Rocío Muñoz-García; Marina Sánchez-Hidalgo; Manuel Alcarranza; María Victoria Vazquéz-Román; María Alvarez de Sotomayor; María Luisa González-Rodríguez; María C. de Andrés; Catalina Alarcón- (MDPI AG, 2023)
Systemic lupus erythematosus (SLE) is a chronic immune-inflammatory disease characterized by multiorgan affectation and lowered self-tolerance. Additionally, epigenetic changes have been described as playing a pivotal role in SLE. This work aims to assess the effects of oleacein (OLA), one of the main extra virgin olive oil secoiridoids, when used to supplement the diet of a murine pristane-induced SLE model. In the study, 12-week-old female BALB/c mice were injected with pristane and fed with an OLA-enriched diet (0.01 % (w/w)) for 24 weeks. The presence of immune complexes was evaluated by immunohistochemistry and immunofluorescence. Endothelial dysfunction was studied in thoracic aortas. Signaling pathways and oxidative-inflammatory-related mediators were evaluated by Western blotting. Moreover, we studied epigenetic changes such as DNA methyltransferase (DNMT-1) and micro(mi)RNAs expression in renal tissue. Nutritional treatment with OLA reduced the deposition of immune complexes, ameliorating kidney damage. These protective effects could be related to the modulation of mitogen-activated protein kinases, the Janus kinase/signal transducer and transcription activator of transcription, nuclear factor kappa, nuclear-factor-erythroid-2-related factor 2, inflammasome signaling pathways, and the regulation of miRNAs (miRNA-126, miRNA-146a, miRNA-24-3p, and miRNA-123) and DNMT-1 expression. Moreover, the OLA-enriched diet normalized endothelial nitric oxide synthase and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-1 overexpression. These preliminary results suggest that an OLA-supplemented diet could constitute a new alternative nutraceutical therapy in the management of SLE, supporting this compound as a novel epigenetic modulator of the immunoinflammatory response.